(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2021)
The current research aims to explore the importance of retail display on consumer impulse buying behavior. Exactly, this paper researched the influence of window display, promotional signage, store layout, background music and store smell on consumer impulse purchase behavior. The research was conducted among 117 customers of Delhi Retail Stores using questionnaire which was formulated based on the previous literature. The collected data was analyzed using factor analysis and linear regression tests. The research findings suggested that store attributes including window display, promotional signage and smell play important role in influencing the impulse buying behavior of customers. Final chapter of the current research provides some recommendations for store managers on further improvement of store atmosphere to encourage impulse buying among customers.